On the evolution of the species complex Pachycondyla chinensis (Hymenoptera: Formicidae: Ponerinae), including the origin of its invasive form and description of a new species - Yashiro, Toshihisa; Matsuura, Kenji; Guénard, Benoit; Terayama, Mamoru; Dunn, Robert R. (Zootaxa, 2010)
Ants are one of the most successful and widespread organisms in the world. Although ants of the genus Pachycondyla (Hymenoptera: Formicidae: Ponerinae) are predominantly tropical in distribution, Pachycondyla chinensis (Emery) is especially abundant in temperate zones in Asia. Recently, P. chinensis has also become an abundant invasive ant species in the United States. However, it was well-known that the Pachycondyla chinensis species complex remained unresolved. Our molecular and morphological results allow us to distinguish two species in the species complex: the species P. chinensis and the new cryptic species P. nakasujii sp. nov., and these two species are widely and sympatrically distributed and abundant in temperate forests in Japan. Moreover, phylogenetic analysis showed that P. chinensis has been introduced into the United States from Japan. In conclusion, our finding of the new species P. nakasujii suggests that much remains undiscovered even in biologically fascinating and well-studied organisms.